A Comprehensive Review of Hepatic Sarcoid - Deutsch-Link, Sasha; Fortuna, Danielle; Weinberg, Ethan M. (Seminars in Liver Disease, 2018)
Sarcoidosis is a multisystem inflammatory disease, which is characterized by the development of noncaseating granulomas amid healthy tissue. While most commonly affecting the mediastinum and/or lungs, sarcoid can also affect the liver, resulting in “hepatic sarcoid.” The spectrum of disease in hepatic sarcoid is variable, ranging from asymptomatic or mild liver enzyme abnormalities to end-stage liver disease requiring liver transplantation. Because clinically-significant hepatic sarcoid is rare, research on epidemiology, clinical manifestations, and treatment is limited. The mainstays of hepatic sarcoid treatment have involved steroids and more recently, ursodeoxycholic acid; however, novel immunomodulatory agents provide new possibilities for management. Questions remain regarding screening, diagnostic modalities, and what to treat with and when. The purpose of this review is to summarize the available research on the epidemiology, clinical course, and management of hepatic sarcoid, and identify gaps in our knowledge to motivate future research.
Keywords: hepatic sarcoid; granulomatous hepatitis; liver sarcoid; sarcoidosis; ursodeoxycholic acid